Long-term Outcome of Adenosine A2A Receptor Antagonist on Lower Urinary Tract Symptoms in Male Parkinson Disease Patients. Issue 3 (May 2018) - Kitta, Takeya; Yabe, Ichiro; Kanno, Yukiko; Higuchi, Madoka; Ouchi, Mifuka; Togo, Mio; Moriya, Kimihiko; Takahashi, Ikuko; Matsushima, Masaaki; Sasaki, Hidenao; Shinohara, Nobuo
Abstract : Objectives: In addition to motor symptoms, bladder dysfunction is a major clinical issue in patients with Parkinson disease (PD). Istradefylline is adenosine A2A receptor antagonist approved for PD patients with wearing-off symptoms. The aim of this study was to determine the long-term effects of istradefylline on lower urinary tract symptoms (LUTSs) in PD patients. Methods: We enrolled 14 male PD patients. The mean age of patients was 73 years (61–77 years), the Hoehn-Yahr stage was 2 (2–3), and disease duration was 9 years (3–28 years). The effects of istradefylline (20 mg/d) on LUTSs in PD patients with motor complications after 3, 6, and 12 months of therapy were evaluated based on the International Prostate Symptom Score and Overactive Bladder Symptom Score before and after its administration. Results: Motor symptoms significantly improved at 12 months' administration (Movement Disorder Society–sponsored revision of the Unified Parkinson's Disease Rating Scale part III: 30.0 ± 12.9 vs 13.8 ± 8.1; P < 0.01). Significant improvements were also observed in the answers provided on urinary questionnaires (International Prostate Symptom Score, 14.4 ± 7.6 vs 8.5 ± 6.8; Overactive Bladder Symptom Score, 6.9 ± 2.8 vs 5.5 ± 3.7; P < 0.05). Nighttime urinary frequency and the percentage of the nocturnal urine volume also improved significantly at 3 months' administration ( P < 0.01). Conclusions: Istradefylline effectively improved not only motor symptoms, but also LUTSs in patients with PD. Abstract : Supplemental digital content is available in the text.